ADVANTAGES AND DISADVANTAGES OF MODERN METHODS OF DIAGNOSIS OF CARDIOVASCULAR DISEASES IN A MODERN INTERPRETATION (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Cardiovascular diseases remain one of the main causes of death in many countries of the world. However, most of these diseases can be prevented or successfully treated, especially if they are detected early. In order to quickly identify any pathology, it is important to know how to properly check the condition of the heart.In this article, we will look at the various methods and tests that can help assess the health of this important organ, what steps you can take to maintain a healthy heart, and what symptoms may indicate potential problems.